2015
DOI: 10.1626/jcs.84.150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flooding on Photosynthesis in Eddo

Abstract: The yield of 'Daikichi', eddo cultivar (Colocasia esculenta Schott (L). var. antiquorum Hubbard & Rehder) cultivar generally grown in upland fields is increased by pot culture under flooded conditions. Here, we studied the effect of flooding on the photosynthesis in eddo under upland field conditions and flooded conditions in which flooding treatment started when two to three leaves emerged. In comparison with upland field conditions, stomatal conductance, transpiration rate, amount of chlorophyll and photosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…Besides, the present study showed that 33 and 56 days of long-term waterlogging increased SPAD (Figure 3), leading to an increase in P n (Figure 2a). The result is consistent with the finding by Ikezawa et al (2015), who demonstrated an increase in SPAD under 94 and 125 days of waterlogging conditions in Eddo. But contrary to that, Li et al (2011) observed chlorophyll degradation under 30 and 90 days of waterlogging in D. chinense.…”
Section: Treatmentsupporting
confidence: 93%
See 1 more Smart Citation
“…Besides, the present study showed that 33 and 56 days of long-term waterlogging increased SPAD (Figure 3), leading to an increase in P n (Figure 2a). The result is consistent with the finding by Ikezawa et al (2015), who demonstrated an increase in SPAD under 94 and 125 days of waterlogging conditions in Eddo. But contrary to that, Li et al (2011) observed chlorophyll degradation under 30 and 90 days of waterlogging in D. chinense.…”
Section: Treatmentsupporting
confidence: 93%
“…Stomatal density was not affected by waterlogging, and thus it may not be involved in increasing g s (Figures 4 and 5e). Ikezawa et al (2015) reported similar results for Eddo and suggested that enhanced stomatal opening is a possible factor for increasing g s under waterlogging. In contrast, Pereira et al (2020) observed that waterlogging adversely affected the development of stomata in soybean, which is a crop susceptible to waterlogging, resulting in a significant reduction in stomatal density.…”
Section: Treatmentsupporting
confidence: 64%
“…The starch content showed a tendency to increase in both raw and steamed mother corm. Photosynthesis was enhanced in the flooding cultivation samples, 10 which, in turn, might have increased the starch content as an assimilation product and affected the physical properties of taro. Furthermore, the tendency of increased stickiness and hardness in mother corms may be responsible for activating starch synthesis during enhanced photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this method, water is supplied continuously for only 3 months during the cultivation period, and it maintains productivity without the injuries caused by continuous cropping. Previous studies have shown that the roots of taro grow normally, without moisture damage, and maintain a high rate of photosynthesis under flooding conditions due to the development of aeration tissue in the roots, similar to that in rice, which results in higher yields 10 . Flooding cultivation also suppresses the damage from nematodes or insects (data not published); therefore, it produces high‐quality and healthy seed cormels.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation